2016
DOI: 10.1186/s12940-016-0089-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the direct occupational and public health impacts of solar radiation management with stratospheric aerosols

Abstract: Geoengineering is the deliberate large-scale manipulation of environmental processes that affects the Earth’s climate, in an attempt to counteract the effects of climate change. Injecting sulfate aerosol precursors and designed nanoparticles into the stratosphere to (i.e., solar radiation management [SRM]), has been suggested as one approach to geoengineering. Although much is being done to unravel the scientific and technical challenges around geoengineering, there have been few efforts to characterize the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…The utility of sulfur injection as a means to mitigate climate change has been long suggested (e.g., Crutzen 2006, Robock et al, 2009Niemeier and Tilmes, 2017), but some potential drawbacks have also been identified (Pongratz et al, 2012;Keller et al, 2014;Effiong and Neitzel, 2016;Irvine et al, 2017). For example, a notable downside of sulfur injection (mostly designed to be initiated from the Tropics to offset the higher intensity of solar radiation there), is that it tends to over-cool the Tropics, while under-cooling the polar warming due to the amplified greenhouse gas effect (Moore et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The utility of sulfur injection as a means to mitigate climate change has been long suggested (e.g., Crutzen 2006, Robock et al, 2009Niemeier and Tilmes, 2017), but some potential drawbacks have also been identified (Pongratz et al, 2012;Keller et al, 2014;Effiong and Neitzel, 2016;Irvine et al, 2017). For example, a notable downside of sulfur injection (mostly designed to be initiated from the Tropics to offset the higher intensity of solar radiation there), is that it tends to over-cool the Tropics, while under-cooling the polar warming due to the amplified greenhouse gas effect (Moore et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For comparison, building and installing enough solar cells to meet global energy demand would, at current prices, cost about USD 250 trillion, although prices are decreasing rapidly (Cassedy and Grossman, 2017). However, apart from moral issues (Robock et al, 2009), sulfate SRM may have damaging effects on human health (Effiong and Neitzel, 2016) and the environment (Pitari et al, 2014;Ward, 2009) that are still poorly understood (Irvine et al, 2017). A sudden discontinuation of SRM will cause rapid warming ("termination shock") to levels dictated by greenhouse-gas concentrations (Brovkin et al, 2009;Matthews and Caldeira, 2007), which could put more stress on ecosystems and societies than a gradual warming (Trisos et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Mimicking large volcanic eruptions, SAI involves deliberate injections of stratospheric sulfate aerosols or their precursor, sulfur dioxide (SO 2 ), to increase Earth's albedo, thereby reducing the amount of incoming solar radiation and lowering surface temperatures. Using climate models, studies have shown that tropical SAI could effectively counteract global warming (e.g., Jones et al, ; ), although it could simultaneously bring unintended effects to the climate system (e.g., Aquila et al, ; Ferraro et al, ; Pitari et al, ), society (e.g., Preston, ; Svoboda et al, ), and human health (e.g., Eastham, ; Effiong & Neitzel, ).…”
Section: Introductionmentioning
confidence: 99%
“…HadGEM2-ES injected 5 Tg/year of SO 2 into the lower stratosphere globally to achieve a global distribution of stratospheric sulfate aerosols amid a lack of realistic stratospheric dynamics (Jones et al, 2010). None of the models have interactive stratospheric ozone chemistry (Eyring et al, 2013 climate system (e.g., Aquila et al, 2014;Ferraro et al, 2014;Pitari et al, 2014), society (e.g., Preston, 2013;Svoboda et al, 2011), and human health (e.g., Eastham, 2015;Effiong & Neitzel, 2016).…”
Section: Introductionmentioning
confidence: 99%